Visual search characteristics of precise map reading by orienteers - Yang Liu (PeerJ, 2019)
This article compares the differences in eye movements between orienteers of different skill levels on map information searches and explores the visual search patterns of orienteers during precise map reading so as to explore the cognitive characteristics of orienteers’ visual search. We recruited 44 orienteers at different skill levels (experts, advanced beginners, and novices), and recorded their behavioral responses and eye movement data when reading maps of different complexities. We found that the complexity of map (complex vs. simple) affects the quality of orienteers’ route planning during precise map reading. Specifically, when observing complex maps, orienteers of higher competency tend to have a better quality of route planning (i.e., a shorter route planning time, a longer gaze time, and a more concentrate distribution of gazes). Expert orienteers demonstrated obvious cognitive advantages in the ability to find key information. We also found that in the stage of route planning, expert orienteers and advanced beginners first pay attention to the checkpoint description table. The expert group extracted information faster, and their attention was more concentrated, whereas the novice group paid less attention to the checkpoint description table, and their gaze was scattered. We found that experts regarded the information in the checkpoint description table as the key to the problem and they give priority to this area in route decision making. These results advance our understanding of professional knowledge and problem solving in orienteering.